REPRODUCTIVE BIOLOGY OF THE RED BIGEYE (Priacanthus macracanthus Cuvier, 1829) IN PALABUHANRATU BAY, INDONESIA - Meuthia Aula Jabbar; Mohammad Mukhlis Kamal; Mennofatria Boer; Ali Suman; I Nyoman Suyasa (Indonesian Fisheries Research Journal, 2018)
The reference point of reproductive biology play an important roles in developing a baseline information for fishery management. Different waters will provide different overview of fisheries related to its biological aspects. The red bigeye (Priacanthus macracanthus) is one of economically important demersal fish species in Indonesia. To support the biological status of this species, a regular field observation were carried out during May 2016 to April 2017 in Palabuhanratu bay, south of West Java. The objective of this study is to estimate the spawning season and potential reproductive stages including to evaluate how the key management related to the species and its gear selectivity. Numbers of red bigeye (Priacanthus macracanthus) specimen was collected from bottom gillnetter and hand liner. Basic information related to length-weigth, bio-reproduction (maturity) were collected regularly to determine GSI, Fecundity and its impact of fishing (Lc, Lm) to evaluate the recent stock status. The result showed sex ratio no significant differences between males and females except in September to December. The growth pattern indicated negative allometric. The predicted of spawning seasons were around June-July and December-January. Mean of fecundity was estimated to be 230,000 ± 178,000 eggs. Management keys were obtained i.e. length at first maturity (Lm) value was to be 21.9 cm TL which is smaller than length at first capture (Lc) 22.4 cm TL for bottom gill netter and 23.1 cm TL for average fishes caught by hand liner. Therefore it is recommended to close the waters in the bay area during the spawning period. In the case of catch, it is important to apply the precautionary approach with emphasizes to the size of fish allowed to be captured more than the Lm value (above 21.9 cm TL).